Dietary kapok seed meal supplementation improved meat quality without adverse effect on growth performance in finishing pigs. Issue 1 (1st January 2018) - Li, Hanlin; Liu, Wenchao; Zhao, Pinyao; Lei, Yan; Kim, Inho
ABSTRACT: Ninety-six crossbred [(Landrace × Yorkshire) × Duroc] finishing pigs with an average initial body weight of 67.02 ± 1.46 kg were used in this 10-week feeding trial to evaluate effect of dietary kapok seed meal (KSM) supplementation in finishing pigs. Pigs were randomly allotted into three dietary treatments (eight replicates/treatment and four pigs/pen). The dietary treatments were: (1) Control (CON), basal diet; (2) K1.5, CON + 1.5% KSM; and (3) K3.0, CON + 3.0% KSM. Overall, average daily feed intake linearly decreased ( P < .05) with the increase in the level of dietary KSM supplementation. KSM groups elevated concentration of low-density lipoprotein in blood at the 10th week ( P < .05). Moreover, meat colour in sensory evaluation linearly increased ( P < .05) as dietary KSM concentration increased. Myristic acid, palmitic acid, stearic acid, linolenic aid, saturated fatty acids (SFAs) and SFAs/polyunsaturated fatty acids ratio linearly increased ( P < .05) as dietary KSM concentration increased, except for palmitoleic acid and oleic acid where the ratio linearly decreased ( P < .05). The present study results indicated that finishing pig supplemented with 3% KSM could improve meat quality and enhance the content of fatty acids of carcass fats and muscle without any adverse effect on growth performance.